André Motte (1936–2021). Belgijski przyjaciel poznańskich filologów i filozofów antycznych - Lewandowski, Ignacy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The author briefly presents the life and work of André Motte (who died 28 November 2021), who was a professor of ancient philology and philosophy at the University of Liège, and details his longtime cooperation with the ancient philologists and philosophers of the Adam Mickiewicz University in Poznań.